Comparative Effects of Two Neutralizing Anti-Respiratory Syncytial Virus (RSV) Monoclonal Antibodies in the RSV Murine Model: Time versus Potency - Mejías, Asunción; Chávez-Bueno, Susana; Ríos, Ana María; Aten, Mónica Fonseca; Raynor, Brett; Peromingo, Estrella; Soni, Perla; Olsen, Kurt D.; Kiener, Peter A.; Gómez, Ana María; Jafri, Hasan S.; Ramilo, Octavio (Antimicrobial Agents and Chemotherapy, 2005)
Classifications Services AAC Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue AAC About AAC Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy AAC RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0066-4804 Online ISSN: 1098-6596 Copyright © 2014 by the American Society for Microbiology. For an alternate route to AAC .asm.org, visit: AAC